Identification and Larvicidal Efficacy of Mosquito-Repelling Plants Used in Malaria Vector Control in South-East Benin - Tante, Camille O; DJENONTIN, TOGNIHOU ARMEL; CHOUGOUROU, CHÈPO DANIEL (My University, 2022)
After identifying issues posed by some synthetic insecticides, the scientific community is now looking for other natural products with insecticidal and/or insect repellent characteristics. This study aimed to identify the plants of the Beninese flora known for their insecticidal and/or insect repellent effects and the indigenous techniques of their use and to evaluate the combined efficacy of extracts of a few on mosquito larvae for the control of malaria vectors in the SouthEast of Benin. A survey was conducted and the insecticidal effects of three combinations made from Azadirachta indica, Cymbopogon nardus and Hyptis suaveolens oils on Anopheles gambiae larvae were studied. The data were analyzed using R software, and Chi-square test was used to compare death rates. Twelve (12) plant species were identified. The combinations of C. nardus and H. suaveolens oils induced the highest mortality rates (90 ± 4.15% and 68 ± 9.14% with stages 2 and 3 larvae, respectively). The application of extracts from these plants to control the malaria vectors population would reduce the use of chemical pesticides, hence the need to promote and enhance the formulations of biopesticides based on plant extracts.
Keywords: Plant species; biopesticides; mosquito-repelling plants; vectors